Carbon dots promote the growth and photosynthesis of mung bean sprouts. (September 2018) - Wang, Huibo; Zhang, Mengling; Song, Yuxiang; Li, Hao; Huang, Hui; Shao, Mingwang; Liu, Yang; Kang, Zhenhui
Abstract: Carbon dots, as one of carbon-based nanomaterials, with excellent fluorescent properties and low toxicity show great potential in bio-science and bio-technology. Here, we grew mung bean sprouts with different concentration of carbon dots (CDs) and studied the plant growth and photosynthesis. We found CDs show a dose-response effect on the growth of mung bean sprouts, including root elongation, stem elongation and biomass. CDs at optimal concentration also promote the root vigor and moisture level of seeds, which may have led to the promotion of plant growth and development. Moreover, mung bean sprouts treated with CDs exhibit an increase up to 21.9% in carbohydrates content compared to the control. We assumed that the increase of carbohydrates might be related to the role of CDs in photosynthesis. Further investigation revealed that CDs can enhance the photosystem activity by improving the electron transfer rate. CDs treatment also affect other critical indicators in photosynthesis, such as chlorophyll content and rubisco activity. These findings show considerable promise in biological research and agriculture production. Graphical abstract: The impact of CDs on the growth of mung bean sprouts, including root, stem and weight. Image 1